Multiple objective optimization of high nitrogen content biofertilizer production using mushroom waste - Amir Syarifudin, Baharudin; Norazwina, Zainol; Nor Hazwani, Aziz (World Researchers Associations, 2025)
The study aimed to optimize nitrogen content in biofertilizer production using mushroom waste. Five factors were analyzed using two-level full factorial design (TLFD) including mushroom waste content, reaction time for Bokashi fermentation, agitation of mushroom waste, size of mushroom waste and drying method. The nitrogen content was measured using a HACH Spectrophotometer. The factors were further optimized using a central composite design (CCD) through response surface methodology. The parameters studied included drying temperature and mushroom waste content.